The Implementation of Water Salinity Tester as a quantitative tool to determine the Total Dissolved Solids in water - Qureshi, Muhammad Abdullah Arif; Tahir, Raja Muhammad (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In the past few years, a water quality testing system has been commonly used in almost every country which is known to have issues related to water contamination. The old system uses the physical inspection of water by taking numerous samples from different water sources. These samples are then verified in the research laboratory using diagnostic technologies. Such techniques are time taking and are not deemed as powerful. Furthermore, new techniques inspect the physical qualities of water and measure the total amount of germs and other infectious items present in the water. Old methods of water testing have drawbacks like complex processing, long result time & low accuracy, etc. So, to eradicate all these issues, we must find out an economical and fast way to determine the quality of water. Such a device is called a “Water Salinity Tester (WST)”. WST is a device that is used to calculate the amount of Total Dissolved Solids (TDS) in water. Developing this sort of tool is to provide equipment that can help the users measure the salinity of water so that it can be controlled if the salinity increases to a certain limit. The tool can be used both domestically and industrially.